Br-LMG/PVB Film: A Novel UVC Dosimeter for Process Monitoring in Chemical and Environmental Engineering - Kye Ryong Ri; Song Taek Kim; Jong Hyok Kim; Guk Chol Kim (Journal of Chemical Engineering Research Progress, 2026)
In chemical engineering processes such as photocatalytic wastewater treatment, cooling water biofouling control, and filling line surface sterilization, confirming UVC dose is critical for process efficiency and safety. However, existing UVC dosimeters rely on complex equipment, acid generators, or high cost, limiting field deployment. This study fabricated a UVC dosimeter based on polyvinyl butyral (PVB) film containing bromo-leuco malachite green (Br-LMG) without any acid generator, and evaluated its dosimetric characteristics for 253.7 nm dose monitoring. Br-LMG/PVB films were prepared by spin-coating and irradiated with UVC doses of 0, 25, 50, 75, 100, 200, and 300 mJ/cm². Changes in optical density, dose-response linearity, post-irradiation stability (30 min and 30 days), and colour difference (ΔE) based on CIE L*, a*, b* were quantified using UV-VIS spectrophotometry and reflectance spectroscopy. Upon UVC irradiation, the film exhibited a maximum absorption peak at 630 nm corresponding to the oxidized form of malachite green. The dose-response curve showed excellent linearity (R² ≈ 1) over 0-300 mJ/cm² with sensitivity of 0.0031 (mJ/cm²)-¹ at 630 nm. After 30 days of room-temperature storage, optical density increased by only 5.2-9.2% without fading. ΔE exceeded 10 at 25 mJ/cm² (perceptible) and reached 18 at 50 mJ/cm² (clearly distinguishable by naked eye). The Br-LMG/PVB film serves as a simple, low-cost, field-deployable UVC dosimeter requiring no additional equipment for dose assessment in chemical and environmental engineering applications. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).